Distribution and Evolution of Nitrogen Fixation Genes in the Phylum Bacteroidetes - Inoue, Jun-ichi (Microbes Environ, 2015)
Diazotrophs had not previously been identified among bacterial species in the phylum Bacteroidetes until the rapid expansion of bacterial genome sequences, which revealed the presence of nitrogen fixation (nif) genes in this phylum. We herein determined the draft genome sequences of Bacteroides graminisolvens JCM 15093(T) and Geofilum rubicundum JCM 15548(T). In addition to these and previously reported ‘Candidatus Azobacteroides pseudotrichonymphae’ and Paludibacter propionicigenes, an extensive survey of the genome sequences of diverse Bacteroidetes members revealed the presence of a set of nif genes (nifHDKENB) in strains of Dysgonomonas gadei, Dysgonomonas capnocytophagoides, Saccharicrinis fermentans, and Alkaliflexus imshenetskii. These eight species belonged to and were distributed sporadically within the order Bacteroidales. Acetylene reduction activity was detected in the five species examined, strongly suggesting their diazotrophic nature. Phylogenetic analyses showed monophyletic clustering of the six Nif protein sequences in the eight Bacteroidales species, implying that nitrogen fixation is ancestral to Bacteroidales and has been retained in these species, but lost in many other lineages. The identification of nif genes in Bacteroidales facilitates the prediction of the organismal origins of related sequences directly obtained from various environments.